Progress in serology and molecular biology of equine parasite diagnosis: sustainable control strategies - Wang, Tengyu; Chen, Xindi; Yan, Xu; Su, Ya; Gao, Wa; Liu, Chunxia; Wang, Wenlong (Frontiers in Veterinary Science, 2025)
Internal parasitic infections are a persistent challenge for horse owners, in the absence of effective vaccines and the growing challenge of drug resistance, leading many researchers to view current control strategies as unsustainable. Despite slow progress over the past two decades, effective parasitic diagnosis remains crucial for controlling infections and preventing the growing issue of drug resistance. This review examines the research progress in serological and molecular biological diagnostic methods for major equine parasites. Currently, most diagnostic techniques are based on genes such as ITS1, ITS2, COI, and IGS, which have been applied to equine strongylids, including Strongylus spp., Cylicocyclus spp., and Cylicostephanus spp. These methods are particularly suitable for large-scale epidemiological studies and rapid species identification. Although many diagnostic methods have been developed, most remain confined to laboratory research and have seldom been used for real-time field diagnostics. Future research should prioritize precise diagnostic methods and clinically applicable alternatives. Additionally, whole genome sequencing has been widely used in eukaryotes for population genetics and the development of diagnostic markers. However, comprehensive genomic data on parasitic species infecting equines is still limited. With the decrease in sequencing costs in the post-genomic era, a growing number of genome assemblies are expected to be released soon. These genome maps will offer comprehensive genomic data to identify specific genetic markers and variations associated with parasitic infections, enabling more accurate and reliable diagnostic techniques. High-throughput sequencing technologies will significantly accelerate progress in equine parasitology research and the development of diagnostic tools like enzyme-linked immunosorbent assay (ELISA) and TaqMan quantitative PCR (qPCR). At the same time, this paper also provides some insights into the research direction of sustainable control programs and equine parasite diagnostic methods.